A Novel Single Nucleotide Polymorphism of Interleukin-10 Gene is Linked to Type 2 Diabetes Mellitus in Iraqi Patients with Toxoplasmosis(Conference Paper ) - Salman, Omar; Maysoon Abdul Zahra Merdaw; Ahmed A. Almaliky (Iraqi journal of pharmaceutical sciences, 2023)
Type 2 diabetes mellitus (T2DM) is a chronic disorder that is a serious health concern all over the globe, it is linked to Interleukin-10 (IL-10) single nucleotide polymorphisms (SNPs) at the promoter region. On the other hand, diabetes influences the cellular and humoral immunity predisposing the patient to a variety of opportunistic parasites one of them is Toxoplasma gondii (T. gondii), which may infect any nucleated cell, including pancreatic cells. The purpose of this research was to explore the association of IL-10 genetic polymorphisms with T2DM and latent toxoplasmosis among Iraqi patients with T2DM. Fifty-five and fifty-eight venous blood samples were taken from T2DM patients and age-matched non-diabetic persons, respectively. Sera from all samples had been tested for the presence of anti-toxoplasma antibodies using the Enzyme-Linked Immunosorbent Assay (ELISA). Polymerase chain reaction (PCR) was performed by specific primers and the products were sequenced at Macrogen /Korea. A higher percentage of T. gondii infection was found in T2DM patients (52.1%) and 31.5% of non-diabetic persons. The high frequency of the SNP at position -3952 among T2DM patients, and this is a novel finding. An interesting result, an increased risk of T2DM was observed in carriers of -1082 A/G variants, which was high frequency among studied subjects. The carriers of both -1082 AG+GG and -3952 AG+GG genotypes had a synergistic effect on the risk of type 2 diabetes mellitus significantly. A significant association between T2DM and polymorphisms at positions -1082 A/G and -3952 A/G of the IL-10 gene.